Mode of Neonatal Delivery Influences the Nutrient Composition of Human Milk: Results From a Multicenter European Cohort of Lactating Women - Samuel, Tinu M.; Thielecke, Frank; Lavalle, Luca; Chen, Cheng; Fogel, Paul; Giuffrida, Francesca; Dubascoux, Stephane; Martínez-Costa, Cecilia; Haaland, Kirsti; Marchini, Giovanna; Agosti, Massimo; Rakza, Thameur; et al. (Frontiers in Nutrition, 2022)
The effect of mode of neonatal delivery (cesarean or vaginal) on the composition of human milk (HM) has rarely been studied. Given the increasing prevalence of cesarean-section (C-section) globally, understanding the impact of C-section vs. vaginal delivery on HM nutrient composition is fundamental. The aim of this study was to evaluate the association between MOD and nutrient composition of HM in the first 4 months of life. Milk samples were obtained from 317 healthy lactating mothers as part of an exploratory analyses within a multicenter European longitudinal cohort to study the HM composition, and potential association with the mode of delivery. We employed traditional mixed models to study individual nutrient associations adjusted for mother’s country, infant birth weight, parity, and gestational age, and complemented it, for the first time, with a multidimensional data analyses approach. Over the first 4 months, nutrient profiles in the milk of mothers who delivered vaginally (n=237) showed significantly higher levels of palmitoleic acid (16:1n-7), stearic acid (18:0), oleic acid (18:1n-9), arachidic acid (20:0), alpha-linolenic acid (18:3n-3), eicosapentaenoic acid (20:5n-3), docosahexenoic acid (22:6n-3), erucic acid (22:1n-9), monounsaturated fatty acids (MUFA) %, calcium and phosphorus, whereas ratios of arachidonic acid/docosahexaenoic acid (ARA/DHA) and n-6/n-3, as well as polyunsaturated fatty acids (PUFA) % were higher in milk from women who had C-sections, in the unadjusted analyses (p<0.05 for all), but did not retain significance when adjusted for confounders in the mixed models. Using a complementary multi dimension data analyses approach (NTF), we show few similar patterns wherein group of mothers with a high density of C-sections showed increased values for PUFA%, n-6/n-3 and ARA/DHA ratios, but decreased values of MUFA%, 20:1n-9, iodine and fucosyl-sialyl-lacto-N-tetraose 2 over the first 4 months of lactation. Our data provides preliminary insights on differences in concentrations of several HM nutrients (predominantly fatty acids) among women who delivered via C-section. Although these effects tend to disappear after adjustment for confounders, given the similar patterns observed using two different data analytical approaches, these preliminary findings warrant further confirmation and additional insight on the biological and clinical effects related to such differences early in life.